2021
DOI: 10.31580/apss.v7i2.1780
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Financial Wellbeing and Mental Health: A Systematic Literature Reviews

Abstract: The aim of this study is to identify and appraise existing relationship between Financial well-being and mental health. Despite abundance of studies on financial wellbeing and mental health, efforts to systematically review this study are still lacking.  This article attempts to fill the gap in understanding and identifies the variables that influences the financial wellbeing and mental health. Systematic literature searches in Psychinfo, Scopus and Google Scholar databases were performed using the combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…This practice enables them to have a better grasp of their financial situation and make informed decisions regarding their spending habits and financial goals. Previous literature support this finding [22,56,60,61].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This practice enables them to have a better grasp of their financial situation and make informed decisions regarding their spending habits and financial goals. Previous literature support this finding [22,56,60,61].…”
Section: Discussionsupporting
confidence: 77%
“…Multiple studies have been conducted to explore the relationship between mental budgeting and financial wellbeing in recent years. A systematic review by [60] identified the importance of proactive prevention, such as financial education and literacy, in reducing the burden of mental depression caused by financial stress. Similarly, mental budgeting was highlighted as a significant factor in promoting positive financial management behaviors, reducing financial stress, and improving financial wellbeing [61].…”
Section: Mental Budgetingmentioning
confidence: 99%